2005
DOI: 10.1186/ar1701
|View full text |Cite
|
Sign up to set email alerts
|

ANKHvariants associated with ankylosing spondylitis: gender differences

Abstract: The ank (progressive ankylosis) mutant mouse, which has a nonsense mutation in exon 12 of the inorganic pyrophosphate regulator gene (ank), exhibits aberrant joint ankylosis similar to human ankylosing spondylitis (AS). We previously performed family-based association analyses of 124 Caucasian AS families and showed that novel genetic markers in the 5' flanking region of ANKH (the human homolog of the murine ank gene) are modestly associated with AS. The objective of the present study was to conduct a more ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 24 publications
3
16
0
2
Order By: Relevance
“…Significantly, we further showed that there are sex differences in the ANKH variants associated with AS 64. Intriguingly, there is heterogeneity even in multiplex AS families.…”
Section: Genetics and Assupporting
confidence: 50%
“…Significantly, we further showed that there are sex differences in the ANKH variants associated with AS 64. Intriguingly, there is heterogeneity even in multiplex AS families.…”
Section: Genetics and Assupporting
confidence: 50%
“…One study identified a sex-specific gene expression profile, showing 291 genes uniquely expressed in female AS patients, 1522 genes expressed in males with AS, and 650 genes expressed in both male and female AS patients compared with healthy matched controls [ 34 •]. Another study revealed that different loci of the ANKH gene were associated with AS in male versus female patient [ 37 ]. The ANKH gene encodes a progressive ankylosing protein, which is involved in the structural damage in axSpA patients.…”
Section: Immunology and Geneticsmentioning
confidence: 99%
“…A study considering the ANKH gene, which encodes a protein that is involved in osteogenesis and plays a role in ankylosis in AS, showed that different loci of the ANKH gene were expressed in men and women with AS [ 22 ]. Furthermore, in multiplex AS families, a specific tissue-non-specific alkaline phosphatase (TNAP) haplotype, which interplays with the ANKH gene in ossification, was associated with AS in men but not in women [ 23 ].…”
Section: Myth 1: Men and Women With Axspa Are Physiologically The Sammentioning
confidence: 99%